2021
DOI: 10.1016/j.breast.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Immediate direct-to-implant breast reconstruction with acellular dermal matrix: Evaluation of complications and safety

Abstract: Objective: Immediate direct-to-implant breast reconstruction with acellular dermal matrix (ADM) is the method of choice for many plastic surgeons and patients, but the use of ADM remains a controversial subject in the literature. This study aimed to investigate complications, reconstructive failure and possible risk factors in directto-implant breast reconstruction with ADM (primarily Strattice™). Methods: We retrospectively examined all patients undergoing immediate direct-to-implant breast reconstruction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Previous studies 26 suggest that surgical removal of the permanent implant can occur up to 1 year after the surgery, and therefore, this is included as a secondary outcome.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 26 suggest that surgical removal of the permanent implant can occur up to 1 year after the surgery, and therefore, this is included as a secondary outcome.…”
Section: Methods and Analysismentioning
confidence: 99%
“…All-cause explantation of the breast implant within 1 year after the breast reconstruction surgery (Y/N) Previous studies 26 suggest that surgical removal of the permanent implant can occur up to 1 year after the surgery, and therefore, this is included as a secondary outcome.…”
Section: Secondary Outcomes Time To Explantationmentioning
confidence: 99%
“…Several surgical options are being employed for breast reconstruction surgery. The use of ADM in implant-based breast reconstruction following mastectomy has received a lot of attention recently (2,83,91,94,104,(107)(108)(109)(110)(111)(112). The advantages of ADM in implant-based breast surgery include implant stabilization, improved aesthetic outcomes, and reduced capsular contracture risks, donor site morbidity, and postoperative pain (34,83,86,109,(112)(113)(114).…”
Section: Breastmentioning
confidence: 99%
“…Since plastic surgery often involves the reformation, filling, or restoration of skin and other soft tissues, ADM materials have also been widely used in plastic surgery due to their unique advantages in soft tissue repair. A report from the American Society of Plastic Surgeons states that ADM was used in > 60% of all breast reconstructions performed in the USA in 2018 [97]. Immediate direct-to-implant breast reconstruction with ADM is the method of choice for many plastic surgeons and patients.…”
Section: Applications In Plastic Surgerymentioning
confidence: 99%
“…Among the reported benefits of ADM are the reduced risk of implant exposure and migration, a more satisfying definition of the inframammary fold, and reduction of the postoperative pain through the increase of the implant-pocket volume and the elimination of the need for coverage from surrounding muscles or fascia [98]. A study reported the acceptable rates of reoperations and implant loss of ADM after investigating the complications, reconstructive failure, and possible risk factors in direct-to-implant breast reconstruction with ADM (primarily Strattice ™ ) [97]. Moreover, breast reconstruction using ADM for the complete coverage of implants has been shown to reduce such complications and improve the aesthetic outcomes [99].…”
Section: Applications In Plastic Surgerymentioning
confidence: 99%